THE INDONESIAN INTER-REGIONAL SOCIAL ACCOUNTING MATRIX FOR FISCAL DECENTRALISATION ANALYSIS - Resosudarmo, Budy P.; Nurdianto, Ditya A.; Hartono, Djoni (Journal of Indonesian Economy and Business, 2009)
Disparities in development have long been a crucial issue in Indonesia. With regard toÂ the new structure of the Indonesian government, it is of great interest to determine whetherÂ Indonesia should further decentralise its budget, and if so, what consequences this wouldÂ have on the national economy overall. This paper develops a simple economic tool â thatÂ is an inter-regional social accounting matrix (IRSAM) multiplier â to analyse the impactsÂ of further decentralising government fiscal policy on regional and national performances.Our simulations show the following. First, reducing gaps among regional economiesÂ and boosting the national economy through a higher fiscal transfer strategy might notachieve the same end; i.e. providing a higher transfer to regions that are lagging behindÂ (Sulawesi and Eastern Indonesia) would most likely reduce gaps among regionaleconomies, but might impact negatively on the national economy overall. Second, inÂ general, a more decentralised fiscal system would benefit households in Sulawesi andEastern Indonesia, whereas the same cannot be said for Java-Bali, Sumatra, andÂ Kalimantan. Third, impacts of further fiscal transfers on labour income vary considerablyÂ depending on the region and type of labour.Keywords: regional economy, fiscal decentralisation, Social Accounting Matrix